Safety and Efficacy of Topical Chitogel- Deferiprone-Gallium Protoporphyrin in Sheep Model - Ooi, Mian L.; Richter, Katharina; Drilling, Amanda J.; Thomas, Nicky; Prestidge, Clive A.; James, Craig; Moratti, Stephen; Vreugde, Sarah; Psaltis, Alkis J.; Wormald, Peter-John (Frontiers in Microbiology, 2018)
Objectives: Increasing antimicrobial resistance has presented new challenges to the treatment of recalcitrant chronic rhinosinusitis fuelling a continuous search for novel antibiofilm agents. This study aimed to assess the safety and efficacy of Chitogel (Chitogel®, Wellington New Zealand) combined with novel antibiofilm agents Deferiprone and Gallium Protoporphyrin (CG-DG) as a topical treatment against S. aureus biofilms in vivo. Methods: To assess safety, 8 sheep were divided into two groups of 7 day treatments (n = 8 sinuses per treatment); (1) Chitogel (CG) with twice daily saline flush, and (2) CG-DG gel with twice daily saline flush. Tissue morphology was analyzed using histology and scanning electron microscopy (SEM). To assess efficacy we used a S. aureus sheep sinusitis model. Fifteen sheep were divided into three groups of 7 day treatments (n = 10 sinuses per treatment); (1) twice daily saline flush (NT), (2) Chitogel (CG) with twice daily saline flush, and (3) CG-DG gel with twice daily saline flush. Biofilm biomass across all groups was compared using LIVE/DEAD BacLight stain and confocal scanning laser microscopy. Results: Safety study showed no cilia denudation on scanning electron microscopy and no change in sinus mucosa histopathology when comparing CG-DG to CG treated sheep. COMSTAT2 assessment of biofilm biomass showed a significant reduction in CG-DG treated sheep compared to NT controls. Conclusion: Results indicate that CG-DG is safe and effective against S. aureus biofilms in a sheep sinusitis model and could represent a viable treatment option in the clinical setting.